2022
DOI: 10.3389/fonc.2022.1057560
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization plus apatinib with or without camrelizumab for unresected hepatocellular carcinoma: A two-center propensity score matching study

Abstract: PurposeTo compare the effectiveness and safety of transarterial chemoembolization (TACE) combined with apatinib and camrelizumab with those of TACE as well as apatinib among patients with unresectable hepatocellular carcinoma (HCC).Materials and methodsThe data of patients with unresectable HCC (uHCC) who received TACE-apatinib-camrelizumab combination (TACE + AC group) and TACE-apatinib combination (TACE + A group) were collected from two centers between January 2018 and January 2022. Propensity score matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In terms of survival benefits, the meta-analysis results of this study showed that compared to the TACE-T, TACE-T-I significantly prolongs the PFS and OS of patients with unresectable HCC, consistent with the results of the included studies. [14][15][16][17][18]23,24,[26][27][28][29][30][31] Subgroup analysis based on different TACE types aligns with the overall pooled results, suggesting that triple treatment regimen may offer better survival benefits for patients with unresectable HCC, unaffected by TACE type. The extension of OS in the TACE-T-I group may be related to the increased ORR, DCR, and Table 3 The meta-analysis results for treatment-related adverse events (TRAEs) of any grade.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In terms of survival benefits, the meta-analysis results of this study showed that compared to the TACE-T, TACE-T-I significantly prolongs the PFS and OS of patients with unresectable HCC, consistent with the results of the included studies. [14][15][16][17][18]23,24,[26][27][28][29][30][31] Subgroup analysis based on different TACE types aligns with the overall pooled results, suggesting that triple treatment regimen may offer better survival benefits for patients with unresectable HCC, unaffected by TACE type. The extension of OS in the TACE-T-I group may be related to the increased ORR, DCR, and Table 3 The meta-analysis results for treatment-related adverse events (TRAEs) of any grade.…”
Section: Discussionmentioning
confidence: 82%
“…Regarding tumor response, the meta-analysis results of this study align with several studies, [14,15,27,28,31] indicating that patients receiving triple therapy (TACE-T-I) exhibit higher ORR and DCR compared to those receiving dual therapy (TACE-T). However, Zhu et al [18] found no significant differences in ORR The study by Sun et al [17] demonstrated that patients receiving triple therapy had a higher ORR than dual therapy (71% vs 42.3%; P = .023), although there was no significant difference in DCR between the 2 groups (93.5% vs 80.8%; P = .195). Also, the study by Jiang et al [16] confirmed better tumor response of patients in the TACE-T-I group than TACE-T group, with a higher ORR (52.4% vs 17.8%; P = .001), but no significant difference in DCR (83.3% vs 77.8%; P = .514).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations